Short Course Monotherapy with Clarithromycin for Localized Mycobacterium Marinum Skin Infection - Mitchell R Weinstein; Donald E Low; Tony Mazzulli (Canadian Journal of Infectious Diseases)
In vitro studies have shown that Mycobacterium marinum is usually susceptible to clarithromycin. However, there are limited published data on the clinical use of clarithromycin for the treatment of M marinum infections. This report describes a previously healthy 58-year-old man who developed a chronic soft tissue infection of his right hand caused by M marinum. He responded to four weeks’ therapy with clarithromycin. Follow-up at six months showed no relapse. Our experience and review of the literature suggest that short course monotherapy with clarithromycin may be quite effective for uncomplicated soft issue infections caused by M marinum.